2019
DOI: 10.1002/aur.2211
|View full text |Cite
|
Sign up to set email alerts
|

Language deficits in specific language impairment, attention deficit/hyperactivity disorder, and autism spectrum disorder: An analysis of polygenic risk

Abstract: Language is one of the cognitive domains often impaired across many neurodevelopmental disorders. While for some disorders the linguistic deficit is the primary impairment (e.g., specific language impairment, SLI), for others it may accompany broader behavioral problems (e.g., autism). The precise nature of this phenotypic overlap has been the subject of debate. Moreover, several studies have found genetic overlaps across neurodevelopmental disorders. This raises the question of whether these genetic overlaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
1
17
0
1
Order By: Relevance
“…This suggests that the association of this SNP with receptive language is not part of a larger behavioral phenotype encompassing ASD, ADHD, familial risk of schizophrenia or bipolar disorder. In this context, it would be useful to note that a study of polygenic risk which used the same cohort used in this study [40] found that a polygenic risk score (PRS) trained on a previous GWAS of SLI was not predictive of the risk of ASD or ADHD in this cohort, but it was predictive of the risk of SLI. The latter resulted in a Nagelkerke's R 2 (adjusted for prevalence and the proportion of cases in the sample) of > 5%, compared to values of close to 0% for ASD and ADHD (see footnote in the Methods section for more information about this).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This suggests that the association of this SNP with receptive language is not part of a larger behavioral phenotype encompassing ASD, ADHD, familial risk of schizophrenia or bipolar disorder. In this context, it would be useful to note that a study of polygenic risk which used the same cohort used in this study [40] found that a polygenic risk score (PRS) trained on a previous GWAS of SLI was not predictive of the risk of ASD or ADHD in this cohort, but it was predictive of the risk of SLI. The latter resulted in a Nagelkerke's R 2 (adjusted for prevalence and the proportion of cases in the sample) of > 5%, compared to values of close to 0% for ASD and ADHD (see footnote in the Methods section for more information about this).…”
Section: Discussionmentioning
confidence: 97%
“…To this end we used the “POE method” as implemented in QUICKTEST v0.99b [ 95 ]. In this analysis, 391 unrelated children were used, the same sample as used in the PRS study [ 40 ] (TROG-2 scores were available for 389 children of those 391 unrelated children). The underlying principle of this approach is the following: assuming that a locus with alleles A and B has an additive effect on a phenotype (the two alleles have different effects on the quantitative trait), the three genotype groups AA, AB and BB will differ in their mean phenotype scores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the strong significance of these findings, this suggests that the genetic architecture of communication disorders maybe largely polygenic, which may additionally explain the lack of replication and/or genome-wide significance. While other studies have examined polygenic risk scores associated with language 15,73 , ours is the first to examine polygenic risk associated with other communication endophenotypes. It is noteworthy that our associated SNPs fell outside of gene coding regions but resided in regulatory regions, even having potential regulatory effects themselves.…”
Section: Discussionmentioning
confidence: 99%
“…A GWA study of SLI identified a nonsense mutation in the gene NOP9, which only resulted in association with the disorder if the gene was paternally inherited, while another locus was identified that was only associated if maternally inherited (Nudel et al, 2014). The same group also demonstrated that genetic variants known to cause SLI do not appear to increase risk of having autism spectrum disorder or attention deficit/hyperactivity disorder (Nudel et al, 2020).…”
Section: Gwa Studiesmentioning
confidence: 99%